Switchbacks Explained: Super-Parker Fields—The Other Side of the Sub-Parker Spiral - Schwadron, N. A.; McComas, D. J. (The Astrophysical journal, 2021)
We provide a simple geometric explanation for the source of switchbacks and associated large and one-sided transverse flows in the solar wind observed by the Parker Solar Probe (PSP). The more radial, sub-Parker spiral structure of the heliospheric magnetic field observed previously by Ulysses, ACE, and STEREO is created within rarefaction regions where footpoint motion from the source of fast into slow wind at the Sun creates a magnetic fieldline connection across solar wind speed shear. Conversely, when footpoints move from the source of slow wind into faster wind, a super-Parker spiral field structure is formed: below the Alfvén critical point, one-sided transverse field-aligned flows develop; above the Alfvén critical point, the field structure contracts between adjacent solar wind flows, and the radial field component decreases in magnitude with distance from the Sun, eventually reversing into a switchback. The sub-Parker and super-Parker spirals behave functionally as opposites. Observations from PSP confirm the paucity of switchbacks within rarefaction regions and immediately outside these rarefaction regions, we observe numerous switchbacks in the magnetic field that are directly associated with abrupt transients in solar wind speed. The magnetic field strength, the radial component of the magnetic field, the speed gradients, radial Alfvén speed, and the ratio of the sound speed to the radial Alfvén speed all conform to predictions based on the sub-Parker and super-Parker spirals within rarefaction regions and solar wind speed enhancements (spikes or jets), respectively. Critically, the predictions associated with the super-Parker spiral naturally explain the observations of switchbacks being associated with unexpectedly large and one-sided tangential flows.